2010
DOI: 10.1007/s10479-010-0727-9
|View full text |Cite
|
Sign up to set email alerts
|

A soft multi-criteria decision analysis model with application to the European Union enlargement

Abstract: This paper proposes a new multi-criteria decision analysis (MCDA) model that uses a series of existing intuitive and analytical methods to systematically capture both objective and subjective beliefs and preferences from a group of decision makers (DMs). A defuzzification method that combines entropy and the theory of displaced ideal synthesizes crisp values from the DMs' subjective judgments. This approach assists the DMs in their selection process by plotting alternatives in a four quadrant graph and conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Note that the raw data of alternatives on criteria could be either qualitative or quantitative in different formats and we should transform them into the unified belief structure in advance. Moreover, similarly to some multiple criteria group decision-making methods (Chin et al, 2009;Fu & Yang, 2010;Huang, Chang, Li, & Lin, 2013;Tavana, Sodenkamp, & Suhl, 2010), we assume that all members of the group accept the common weights of criteria, i.e., ω = (ω 1 , ω 2 , . .…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Note that the raw data of alternatives on criteria could be either qualitative or quantitative in different formats and we should transform them into the unified belief structure in advance. Moreover, similarly to some multiple criteria group decision-making methods (Chin et al, 2009;Fu & Yang, 2010;Huang, Chang, Li, & Lin, 2013;Tavana, Sodenkamp, & Suhl, 2010), we assume that all members of the group accept the common weights of criteria, i.e., ω = (ω 1 , ω 2 , . .…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Sundarraj (2006) suggests that because decision-makers specifying preferences in distributed locations will make incorrect decisions when utilizing the AHP approach, many organizations' applications of the AHP approach vary significantly. Tavana, Sodenkamp & Suhl (2010) noted that there has been criticism of AHP in the operations research literature, including preference reversals, because of the questionable theoretical basis.…”
Section: Fuzzy Preference Relationsmentioning
confidence: 99%
“…Sundarraj (2006) discussed that because of decision-makers specifying the preferences in distributed locations will make wrong decision when utilizing AHP approach, many organizations tend to apply AHP approach vary considerably. Moreover, Tavana et al (2010) concluded that there has been some criticism of the AHP in the operations research literature including preference reversals because of questioned the theoretical basis, and therefore, they proposed a new multi-criteria decision analysis model to avoid the controversies associated with rank reversal. Following this, Herrera-Viedma et al (2004) proposed consistent fuzzy preference relations for establishing pairwise comparison-preference decision matrices using the additive reciprocal transitivity property that can address the consistency problem and certain other drawbacks of AHP.…”
Section: Consistent Fuzzy Preference Relationsmentioning
confidence: 99%